New Hydrolyzable Tannin with Potent Antioxidant and α-Glucosidase Inhibitory Activity from Black Tea Produced from Camellia taliensis - Min Chen; Na Li; Hong-Tao Zhu; Man Zhang; Zhao-Hong Duan; Dong Wang; Chong-Ren Yang; Ying-Jun Zhang (Foods, 2023)
Camellia taliensis (W. W. Smith) Melchior, belonging to the genus Camellia sect. Thea., is mainly distributed from northern Myanmar to western and southwestern Yunnan province of China, and its leaves have been used to make various teas by the locals of its growing regions. The chemical constituents of C. taliensis are significantly related to those of cultivated tea plants, C. sinensis and C. sinensis var. assamica. The HPLC-ESI-MS analysis of black tea prepared from the leaves of C. taliensis showed a rich existence of polyphenols. Further comprehensive chemical study led to the separation and recognition of 32 compounds (1–32), including one new hydrolyzable tannin, 1-O-galloyl-4,6-tetrahydroxydibenzofurandicarboxyl-β-D-glucopyranose (1), and one new natural product (24). The known compounds referred to seven hydrolyzable tannins (2–8), 10 flavonols and glycosides (9–18), and 14 simple phenolics (19–32). Their structures were elucidated by comprehensive spectroscopic analyses. Among them, 20 compounds (2, 3, 6, 7, 8, 15, 17, 18, 20–22, 24–32) were isolated from black tea for the first time. Most isolates displayed obvious antioxidant activities on DPPH and ABTS+ assays, and the hydrolyzable tannins 1, 3–5, 7, and 8 exhibited stronger inhibitory activities on α-glycosidase than quercetin and acarbose (IC50 = 5.75 and 223.30 μM, respectively), with IC50 values ranging from 0.67 to 2.01 μM.